2021
DOI: 10.1007/s10571-021-01121-3
|View full text |Cite
|
Sign up to set email alerts
|

Altered MicroRNA Expression in Intracranial Aneurysmal Tissues: Possible Role in TGF-β Signaling Pathway

Abstract: The molecular mechanisms behind the rupture of intracranial aneurysms remain obscure. MiRNAs are key regulators of a wide array of biological processes altering protein synthesis by binding to target mRNAs. However, variations in miRNA levels in ruptured aneurysmal wall have not been completely examined. We hypothesized that altered miRNA signature in aneurysmal tissues could potentially provide insight into aneurysm pathophysiology. Using a high-throughput miRNA microarray screening approach, we compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…It is worth mentioning that many of these differentially expressed miRNAs (including miR-143, miR-145, miR-21, miR-26, miR-29a/b, miR-146a, miR-155, miR-133a, miR-133b, and let-7 family) are also altered in abdominal aortic aneurysmal tissues [50][51][52][53] suggesting a common mechanism. Interestingly, the levels of several miRNAs (e.g., miR-143, miR-145, and miR-23b) were found to be consistently down-regulated among the studies described above [30,45,47,54]. For example, miR-23b was reduced in IA tissues and was reported to target phosphatase and tensin homolog (PTEN) [55], a key regulator of proliferation, differentiation, and cytokine production during pathological vascular remodeling in smooth muscle cells [56].…”
Section: Mirna In Intracranial Aneurysmal (Ia) Tissue and Subarachnoid Hemorrhagementioning
confidence: 96%
See 4 more Smart Citations
“…It is worth mentioning that many of these differentially expressed miRNAs (including miR-143, miR-145, miR-21, miR-26, miR-29a/b, miR-146a, miR-155, miR-133a, miR-133b, and let-7 family) are also altered in abdominal aortic aneurysmal tissues [50][51][52][53] suggesting a common mechanism. Interestingly, the levels of several miRNAs (e.g., miR-143, miR-145, and miR-23b) were found to be consistently down-regulated among the studies described above [30,45,47,54]. For example, miR-23b was reduced in IA tissues and was reported to target phosphatase and tensin homolog (PTEN) [55], a key regulator of proliferation, differentiation, and cytokine production during pathological vascular remodeling in smooth muscle cells [56].…”
Section: Mirna In Intracranial Aneurysmal (Ia) Tissue and Subarachnoid Hemorrhagementioning
confidence: 96%
“…In addition, miRNAs are aberrantly expressed in the vascular walls following injury [42]. Several studies have confirmed that miRNAs are dysregulated in intracranial aneurysms (Table 1) [30,[44][45][46][47][48]. In 2014, Liu et al reported that over 150 miRNAs were differentially expressed in aneurysmal arteries compared to normal arteries [30], demonstrating both patterns of up-and down-regulation of various miRNAs.…”
Section: Mirna In Intracranial Aneurysmal (Ia) Tissue and Subarachnoid Hemorrhagementioning
confidence: 99%
See 3 more Smart Citations